The metaphysics of the mechanical image of the world - Aulestia Calero, Martín (2023)
This article develops the fundamental lines of what I have called, following in the open road of Martin Heidegger, the "destruction of the metaphysics of the mechanical image of the world". To do so, it first shows the essential relationship between our understanding of technique and the meaning of the modern epoch. In this order of ideas, the problem of the type of link that we should recognize between modern technology and science is developed. With all these items, we point out that, at the heart of the technoscientific project, is the Baconian idea that nature must be known in order to be mastered. The latter shows that, despite the undeniable and profound transformations of technoscience, especially since the twentieth century, there has been no comparable modification at the level of its metaphysical foundation. We conclude showing the basic suggestions of our thesis that technology must be seen today as politics.